Frequency of affected teeth in pediatric patients with molar hypomineralisation - Biondi , Ana María (2026)
Molar hypomineralisation (MH) was defined as a systemic pathology that affects one or all of the first permanent molars, often involving incisors. Objectives: To estimate the frequency of affected teeth in patients with MH who attended the Faculty of Dentistry University of Buenos Aires. Materials and Methods: An observational, cross-sectional, and descriptive study was conducted on children with complete dentition who received treatment at the Pediatric Department April-August 2024. Faculty members performed clinical diagnoses with a Kappa value of 0.87, using the Mathu-Muju and Wright criteria. Recorded data included sex, age, presence of MH, and tooth severity levels, analyzed through means, percentages, and odds ratio. Results: The study comprised 173 patients, mean age of 14±1.6 years, 58.39% female. Among the participants, 27.74% (CI 21.35-35.14) had MH, mean age 13.54±1.86 years and 66.7% being female. Lesions were observed across all dental groups. First permanent molars were affected in 54.69% of cases (CI 47.34-61.89), followed by incisors at 17.26% (CI 13.63-21.42), second molars at 12.5% (CI 8.16-18.04), first premolars and canines at 10.94% (CI 6.89-16.25), and second premolars at 8.85% (CI 5.23-13.81). Of the lesions observed, 87.84% were classified as mild, 8.23% as moderate, and severe lesions were identified only in the first (1.96%) and second molars (1.96%). Upper incisors were found to be more affected than lower incisors (OR 5.38). Conclusions: In this sample, although the first molars and incisors were the most affected, all dental groups displayed lesions, with the second molars showing the highest frequency.